STRATEGIES FOR STRENGTHENING SOFT SKILLS IN TECHNOLOGY EDUCATION PROGRAMMES IN RIVERS STATE: A ROADMAP FOR EMPLOYMENT OPPORTUNITIES FOR TECHNICAL EDUCATION GRADUATES (NAU Journal of Technology and Vocational Education, 2025)
The study sought to investigate strategies for strengthening soft skills in technology education programme in Rivers State: A roadmap for employment opportunities for technical education graduates. Three research questions guided the study. The study adopted survey research design. The population of the study was one hundred and seven (107) technology educators. There was no sampling due to the small size of the population. The instrument used for data collection was a 24-item structured questionnaire which was face and content validated by three experts in the Department of Technology Education, Rivers State University, Port Harcourt. Cronbach Alpha reliability method was employed to determine the internal consistency of the instrument which yielded a coefficient of 0.85. Mean and standard deviation were the statistical tools used to answer the research questions. The result of the study revealed that there are soft skills in technology education programme in Rivers State that are needed to be strengthened as a roadmap for employment opportunities for technical education graduates. It was therefore recommended among others that technology educators whose duty is to train technical education students to acquire soft skills for employment opportunities upon graduation should ensure that these soft skills are properly imparted on the students during the period of their training in the school.
Keywords: Strengthening; soft skills; roadmap; employment; opportunities